Determination of δ44/40Ca and δ56/54Fe in Geological Materials Combined with a Simplified Method for their Separation Using a Single TODGA Resin Column. Issue 4 (18th September 2020) - Guan, Qiuyun; Sun, Yali; Zhang, Zhaofeng; Liu, Xiaoming; An, Yajun; Liu, Fang; Zhao, Shouqian
Abstract : A measurement procedure has been developed for the determination of δ 44/40 Ca and δ 56/54 Fe in geological samples by multi‐collector inductively coupled plasma‐mass spectrometry (MC‐ICP‐MS) and thermal ionisation mass spectrometry (TIMS), combined with a single TODGA resin column for their separation. Using the TODGA resin for separation of geological materials, Fe and Ca ions were eluted by using 8 ml of 1.5 mol l −1 HNO3 and 8 ml of 2 mol l −1 HCl, respectively, and their recovery was 99.7 ± 0.4% ( n  = 3) for the former and 99.4 ± 0.6% ( n  = 3) for the latter after removal of matrix and interfering elements using 12 ml of 6 mol l −1 HCl. This procedure was validated by the reference materials AGV‐2, BCR‐2 and BHVO‐2. Their Fe and Ca isotope data were comparable to their literature values, confirming a single column containing TODGA resin can be applied to the separation of Fe and Ca in geological samples for determination of their isotope ratios free of measurement bias. Key Points: A single TODGA resin column separation method was developed for Fe and Ca isotope determinations. Fe and Ca were effectively separated from interfering elements with high recoveries, avoiding isotope fractionation during chemical separations. Data for geological reference materials were consistent with their literature values.